The Extrinsic and Intrinsic Roles of PD-L1 and Its Receptor PD-1: Implications for Immunotherapy Treatment - Hudson, Katie; Cross, Neil; Jordan-Mahy, Nicola; Leyland, Rebecca (Frontiers in Immunology, 2020)
Programmed death-ligand 1 (PD-L1) is an immune checkpoint inhibitor that binds to its receptor PD-1 expressed by T cells and other immune cells to regulate immune responses; ultimately preventing exacerbated activation and autoimmunity. Many tumours exploit this mechanism by overexpressing PD-L1 which often correlates with poor prognosis. Some tumours have also recently been shown to express PD-1. On tumours, PD-L1 binding to PD-1 on immune cells promotes immune evasion and tumour progression, primarily by inhibition of cytotoxic T lymphocyte effector function. PD-1/PD-L1-targeted therapy has revolutionised the cancer therapy landscape and has become the first-line treatment for some cancers, due to their ability to promote durable anti-tumour immune responses in select patients with advanced cancers. Despite this clinical success, some patients have shown to be unresponsive, hyperprogressive or develop resistance to PD-1/PD-L1-targeted therapy. The exact mechanisms for this are still unclear. This review will discuss the current status of PD-1/PD-L1-targeted therapy, the new and emerging tumour-intrinisic roles of PD-L1 and its receptor PD-1 and how they may contribute to tumour progression and immunotherapy responses as shown in different oncology models.